GRANITIZATION OF AMPHIBOLITES. 1. RESULTS OF FIRST EXPERIMENTS WITH FLUID FILTERING THROUGH ROCK - Khodorevskaya L.I.; Shmonov V.M.; Zharikov V.A. (My University, 2003)
The filtration of silicic-alkaline fluid through amphibolite is reproduced experimentally at a temperature of 750°C and a total pressure of 5 kbar, which enables modeling amphibolite granitization in an open system. The infiltration-controlled effect of high-temperature silicic-alkaline fluid, which is in equilibrium with granite, on amphibolite results in the development of a miniature granitization zoning column corresponding to the infiltration-controlled type of the process in an open system. The granitization column consists of (a) an outer zone of biotitized amphibolite, (b) intermediate zone of more intensely feldspathized, bleached, and debasified amphibolite with partial granitic melt in the interstitial space (zone soaked by melt), and (c) a zone of complete replacement by melt. The physicochemical characteristics of the country rocks (their porosity and permeability) are determined. Debasification of the country rock under the effect of fluid is demonstrated to proceed with a higher rate than rock replacement by melt.